2004
DOI: 10.1074/jbc.m401089200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Mutational Analysis of Heparan Sulfate 3-O-Sulfotransferase Isoform 1

Abstract: Heparan sulfate interacts with antithrombin, a protease inhibitor, to regulate blood coagulation. Heparan sulfate 3-O-sulfotransferase isoform 1 performs the crucial last step modification in the biosynthesis of anticoagulant heparan sulfate. This enzyme transfers the sulfuryl group (SO 3 ) from 3-phosphoadenosine 5-phosphosulfate to the 3-OH position of a glucosamine residue to form the 3-O-sulfo glucosamine, a structural motif critical for binding of heparan sulfate to antithrombin. In this study, we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 39 publications
5
74
0
1
Order By: Relevance
“…In addition, a ternary complex of 3-OST-3/PAP/tetrasaccharide substrate was solved at 1.9Å (46,47). We have found that 3-OST-1 and 3-OST-3 have very similar overall structure.…”
Section: Crystal Structures Of 3-ost-1 and 3-ost-3mentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, a ternary complex of 3-OST-3/PAP/tetrasaccharide substrate was solved at 1.9Å (46,47). We have found that 3-OST-1 and 3-OST-3 have very similar overall structure.…”
Section: Crystal Structures Of 3-ost-1 and 3-ost-3mentioning
confidence: 94%
“…Because 3-OSTs play a critical role in controlling the biosynthesis of anticoagulant HS and unique substrate specificities among the isoforms, we investigated the mechanism of 3-OSTs using a structural biology approach coupled with site-directed mutagenesis (46,47). From these studies, several key amino acid residues have been identified that contribute to the interactions with the sulfo donor PAPS, as well as with polysaccharide substrates.…”
Section: Crystal Structures Of 3-ost-1 and 3-ost-3mentioning
confidence: 99%
“…N-sulfotransferase (NST), C 5 -epi, 2-OST, 6-OST-1, 6-OST-3, 3-OST-1, 3-OST-5, and N-acetyl-D-glucosaminyl transferase of E. coli K5 strain (KfiA) were expressed and purified as previously described (6,(13)(14)(15)(16). PmHS2 was expressed as an N-terminal fusion to His 6 using a PET-15b vector (Novagen) (17).…”
Section: Methodsmentioning
confidence: 99%
“…AF019385.1; amino acids sequence from G48 to H311) [8] was codon optimized and synthesized by Integrated Device Technology, Inc. (USA) and cloned into the pIDTSMART plasmid with a 5′ overhang containing an XbaI site, a 3′ overhang containing an SmaI site, and a 6× His-tag fused at the N-terminus of expressed protein. The pIDTSMART-3-OST-1 plasmid was double digested using XbaI and SmaI restriction enzymes (Fermentas, USA), and the digested 3-ost-1 gene was ligated into the E. coli-B.…”
Section: Methodsmentioning
confidence: 99%
“…2c). To compare the sulfotransferase activity to that in E. coli-expressed 3-OST-1 constructed previously in another lab [8], we negated the background sulfotransferase activity by subtracting out the measurements from non-induced samples. The measurements for B. megaterium are not in units of micromolar PNP/ milligram protein because no protein concentration measurement was taken as we were only looking for activity qualitatively.…”
Section: Activity Of Expressed Enzymementioning
confidence: 99%